Prescribing pattern of antidiabetic drugs in type 2 diabetes mellitus at a tertiary care hospital in Eastern India - Das, Alak K.; Dutta, Aishwarya; Maitiy, Animesh; Sarkar, Dipak K.; Nandy, Manab; Ghosh, Jinia (International Journal Of Community Medicine And Public Health, 2021)
Background: Chronic hyperglycemia of diabetes mellitus (DM) is associated with long-term damage, dysfunction and failure of various organs, especially the eyes, kidneys, nerves, heart and blood vessels. We aimed to evaluate the prescribing pattern of antidiabetic drugs among Type 2 DM (T2DM) outpatients in Medical College, Kolkata. Methods: A cross sectional study was conducted over a period of three months in the Department of Pharmacology and Department of Endocrinology, Medical College, Kolkata. Detailed information of the participants regarding demography, medical history, duration of diabetes, family history of diabetes, prescribed antidiabetic medicines, comorbid conditions and associated medications were evaluated. Results: A total of 305 subjects with T2DM were included and 516 prescriptions were analyzed. 57% of the subjects were male. Majority of patients the were in the age group of 51-60 (37.7%) years. Most of them had history of diabetes between 1-5 years (46.26%) and most common comorbid condition was hypertension. The average number of antidiabetic medicines per prescription was 2.90. Antidiabetic drug was prescribed as monotherapy (5.23%) as well as combination of two (32.36%), three (38.17%), four (16.47%), five (7.17%) and six (0.58%) anti-diabetic drugs combinations. Among the oral antidiabetic (OAD) agents, metformin was most commonly prescribed (92.44%) while the most commonly prescribed injectable antidiabetic medicine was lispromix insulin (27.13%). Conclusions: The antidiabetic medicine prescribing trend appeared to be shifting towards combination therapy. Through a thorough understanding of the existing prescribing patterns, attempts may be made to improve the quality and efficiency of drug therapy.